Expression of ovine gamma interferon in Escherichia coli and Corynebacterium glutamicum. - Billman-Jacobe, H (1994)
Bacteria of two species, Escherichia coli and Corynebacterium glutamicum, were used as hosts to express recombinant ovine gamma interferon as a fusion protein with glutathione S-transferase. The recombinant gamma interferon produced by both bacteria was biologically active in vitro and was recognized by anti-gamma interferon monoclonal antibodies. E. coli produced large amounts of soluble recombinant protein which could be purified by a simple affinity chromatography method. Only a small fraction of the recombinant protein made by C. glutamicum was recovered by this method. Expression of recombinant protein in C. glutamicum was unstable but could be controlled by increased regulation of the tac promoter. Both hosts expressed ovine gamma interferon at high levels, with the recombinant protein making up a significant proportion of the cellular protein content.